A Dataset and TinyML Model for Coarse Age Classification Based on Voice Commands - Kadir A.D.I.A.; Al-Haiqi A.; Din N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Classification (of information); Data acquisition; Internet of things; Learning systems; Statistical tests; Age classification; Arduino nano BLE 33 sense; Data collection; Data preprocessing; Edge impulse; Machine learning models; Machine-learning; Sub-disciplines; Tiny machine learning; Voice command; Deep learning